Implementasi Peraturan Walikota Lhokseumawe Nomor 32 Tahun 2021 Tentang Pencegahan dan Penanganan Stunting di Kecamatan Muara Dua : Pengabdian - Fadillah, Fadillah; Ti Aisyah; Syamsuddin, Syamsuddin; Muklir, Muklir; Fahmi, Asrul (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Stunting remains a serious health problem in Indonesia, including in Lhokseumawe City. This study aims to examine the implementation of stunting prevention and management programs at Muara Dua Community Health Center (Puskesmas) and to analyze the inhibiting factors. A qualitative approach was used through observation, interviews, and documentation. The results show that the program is carried out through nutrition counseling, provision of supplementary food and vitamins, monitoring child growth at posyandu, home visits, and nutrition counseling for pregnant and breastfeeding mothers. The roles of health workers, posyandu cadres, and village officials are significant, and continuous education improves community knowledge about child nutrition and health. However, the program still faces challenges such as low community awareness, limited facilities, participation dependent on incentives, and data recording issues. Cultural factors and misconceptions about short stature also slow program achievements. Effective communication strategies, improved facilities, and optimal resource management are needed to enhance program implementation.